2010
DOI: 10.2105/ajph.2009.179697
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Psychopathology in the Wake of Civil War: Long-Term Posttraumatic Stress Disorder in Nimba County, Liberia

Abstract: The demonstration of a "path of PTSD" coincident with the decades-old path of violence dramatically underscores the direct link between population burden of psychopathology and the experience of violent conflict. Persistent postconflict disruptions of social and physical context may explain some of the observed patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 20 publications
2
26
3
Order By: Relevance
“…Dejong et al [20] revealed that the relatively high prevalence of PTSD, 34% in Algeria compared to other areas under that study may be due to the fact that terrorist attacks were still ongoing during the time of their data collection. Other socio-demographic variables such as ethnicity, religion, and occupation were not significantly associated with PTSD in both groups as against previous studies that have demonstrated this association [6,9] . Worthy of note is the fact that the samples were drawn from populations not displaced by the conflict or other traumatic events in the case of the control group and therefore had their social structure and cultural institutions preserved.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Dejong et al [20] revealed that the relatively high prevalence of PTSD, 34% in Algeria compared to other areas under that study may be due to the fact that terrorist attacks were still ongoing during the time of their data collection. Other socio-demographic variables such as ethnicity, religion, and occupation were not significantly associated with PTSD in both groups as against previous studies that have demonstrated this association [6,9] . Worthy of note is the fact that the samples were drawn from populations not displaced by the conflict or other traumatic events in the case of the control group and therefore had their social structure and cultural institutions preserved.…”
Section: Discussioncontrasting
confidence: 63%
“…In particular, the prevalence of PTSD found among the post conflict survivors (55.5%) was similar to the 24.8-54% current prevalence found among post conflict survivors in Rwanda [11] , Lebanon [8] , Liberia [9] and Uganda [10] , but higher than the 10-15.1% found in Northern-Ireland [6] , and Turkey [7] , following exposure to mass violence in these countries. Similarly, the rate in the group not exposed to conflict was close to the 9.4% prevalence of current PTSD reported among the Israeli general population [5] .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This possibility is consistent with other studies, where alcohol use has been associated with nearly 4% of all-cause mortality; furthermore, the attributable disease burden is most prominent among marginalized populations (Casswell & Thamarangsi, 2009; In the last decade, recognition of alcohol use and mental illness as neglected public health issues in low-resource countries has led to a call for action (Patel et al, 2009). In Liberia, several studies estimate a high prevalence of mental illness (Galea et al, 2010;Johnson et al, 2008). Alcoholism is frequently co-morbid with depression and PTSD, and this has been found to be characteristic of other African post-conflict populations (Okulate & Jones, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…to Galea et al (2010) and Lever, Pinol, & Uralde (2005), strong internal relationships build a positive perception of community which can overcome even the psychological effects of poverty and war which appears to be the case in Banteay Chhmar.…”
Section: The Role Of Resident Perceptions In Cbtmentioning
confidence: 95%